Perbandingan Analisis Prediksi Kebangkrutan Menggunakan Model Altman Z-Score Dan Model Logistik (Studi Empiris Pada Perusahaan Non Keuangan Yang Terdaftar Di Bei) - Frenciscka Kristin; Haryetti '; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to compare bankruptcy of prediction modelbetween Almtan Z-Score and Logistics models. We use secondary data which get from Indonesian Capital Market Directory (ICMD). Purposive sampling is used to get the sample. T-test paired sample is use to analyse the data. The result shows that both of the model have difference result in predicting of bankruptcy. Furthermore we suggest to use Altman model to predict bankruptcy because the result is more accurate than the logistics model.Keywords: Altman Z-score and Logistic, bankruptcy